2011
DOI: 10.1002/ejic.201101142
|View full text |Cite
|
Sign up to set email alerts
|

Hexaphosphine: A Multifaceted Ligand for Transition Metal Coordination

Abstract: We report the synthesis and characterization of the first ferrocenyl polyphosphane incorporating six phosphorus donor atoms. In this unique ligand, the cyclopentadienyl rings of the ferrocenyl backbone adopt a staggered position, which leads to a piano-stool arrangement for each of the two sets of three P atoms facing the same direction. As a consequence [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…The weak interaction existing in [ 1b ] between the Pd(0) center and the phosphane group from the lower Cp ring is consistent with NMR and kinetic observations reported early on . In addition, the fairly short internuclear distance observed in the precursor Pd(II) complex 1 (Pd···P3 = 3.763 Å, sum of van der Waals (Pd,P) radii = 3.43 Å) is a favorable structural feature, as it was previously experimentally observed in related complexes that such similar distances (Pd···P) can be shorten down to 2.618 Å . Additionally, the shuttling of Pd(II) center between three phosphorus centers in such arrangement and the stabilization of the related Pd(0) intermediates by tridentate coordination have been also documented by density functional theory (DFT) calculations …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The weak interaction existing in [ 1b ] between the Pd(0) center and the phosphane group from the lower Cp ring is consistent with NMR and kinetic observations reported early on . In addition, the fairly short internuclear distance observed in the precursor Pd(II) complex 1 (Pd···P3 = 3.763 Å, sum of van der Waals (Pd,P) radii = 3.43 Å) is a favorable structural feature, as it was previously experimentally observed in related complexes that such similar distances (Pd···P) can be shorten down to 2.618 Å . Additionally, the shuttling of Pd(II) center between three phosphorus centers in such arrangement and the stabilization of the related Pd(0) intermediates by tridentate coordination have been also documented by density functional theory (DFT) calculations …”
Section: Resultssupporting
confidence: 86%
“…14 In addition, the fairly short internuclear distance observed in the precursor Pd(II) complex 1 (Pd•••P3 = 3.763 Å, 34 sum of van der Waals (Pd,P) radii = 3.43 Å) is a favorable structural feature, as it was previously experimentally observed in related complexes that such similar distances (Pd•••P) can be shorten down to 2.618 Å. 35 Additionally, the shuttling of Pd(II) center between three phosphorus centers in such arrangement and the stabilization of the related Pd(0) intermediates by tridentate coordination have been also documented by density functional theory (DFT) calculations. 36 Concerning the OA process, two pathways are envisioned from the isomeric palladium complexes [1a] or [1b]; however, their relative contribution to k app cannot be distinguished from these kinetic experiments.…”
Section: ■ Results and Discussionmentioning
confidence: 53%
“…The SSCCs values of 34.5 Hz for 4a (Fu, Ph) and 17.1 Hz for 4b (Fu, i -Pr) cannot be associated with classical 4 J PP coupling constants that are transmitted through covalent bonding. Additionally, their magnitude nicely correlates the SSCCs found in related constrained ferrocenic polyphosphines holding three or four magnetically inequivalent nearby phosphino groups. ,, …”
Section: Resultssupporting
confidence: 62%
“…However, advanced NMR studies have shown that scalar spin couplings between two proximate spin active nuclei (A, B) can commonly operate through nonbonded interactions, leading to J AB coupling constants relating thus to " ug -p e" e u le scalar p − p upl g transmission (TS couplings). 7,6b-l Such often neglected TS p − p upl g process is recurrent and involved in all commonly encountered spin active nuclei for NMR studies, such as 1 H, 13 C, 19 F, and 31 P, non-exhaustively.…”
Section:  Introductionmentioning
confidence: 99%
“…Only few ferrocenyl phosphine ligands of higher rank than diphosphines are known. While ferrocene derivatives substituted with three or four groups incorporating donor atoms were early on developed in our group, we extended cyclopentadienyl functionalization to the introduction of three phosphino groups based on three successive sequences of phosphination/lithiation of cyclopentadienyllithium . The tris‐(diphenylphosphino) cyclopentadienide lithium salt Z was obtained from F in 56 % yield (Figure ).…”
Section: The Icing On the Cake: The Ferrocene Hexaphosphine And Itmentioning
confidence: 99%